1995
DOI: 10.1177/096032719501400706
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that the blood/brain barrier impedes paraquat entry into the brain

Abstract: The distribution of the non-selective herbicide paraquat was examined in the brain following subcutaneous admin istration of 20 mg kg -1 paraquat ion containing [14C]paraquat to male adult rats in order to determine whether paraquat crosses the blood/brain barrier. Following administration, [14C]paraquat reached a maxi mal concentration in the brain (0.05% of administered dose) within the first hour and then rapidly disappeared from the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 19 publications
3
31
1
Order By: Relevance
“…Several studies now agree that PQ penetration into the brain is an age-dependent phenomenon. Higher PQ levels can be found in neonatal brains compared with brain regions of adult and elderly rats, 32 or in either very young (2 weeks old) or very old (12 and 24 months old) animals when compared with normal adult (3-month-old rats). 34,35 Thus, it is apparent that neonatal or very young animals are better able to sequester PQ.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies now agree that PQ penetration into the brain is an age-dependent phenomenon. Higher PQ levels can be found in neonatal brains compared with brain regions of adult and elderly rats, 32 or in either very young (2 weeks old) or very old (12 and 24 months old) animals when compared with normal adult (3-month-old rats). 34,35 Thus, it is apparent that neonatal or very young animals are better able to sequester PQ.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 98%
“…After a single administration, most of the PQ that reaches the brain is apparently associated with structures outside the BBB (i.e., the pineal gland and the cerebral ventricles) or with three areas of the brain: the anterior portion of the olfactory bulb, the hypothalamus and the area postrema, which do not have a tight BBB. 32 Shimizu and colleagues 33 challenged these initial observations. Using a brain microdialysis technique in rats, they showed that PQ could be found in the dialysate after subcutaneous administration.…”
Section: Pq Toxicity In Animal Models and The Underlying Mechanismsmentioning
confidence: 99%
“…Early studies suggested that the pharmacokinetic properties of paraquat made it an unlikely candidate due to its low partition coefficient, limited absorption and poor CNS penetration [27]. In addition paraquat showed little penetration into the brain structures of rats with an intact blood-brain barrier [28,29]. More recent studies, however, have reported the ability of paraquat to cross the blood-brain barrier, possibly via the neutral amino acid transporter [30], and to accumulate in certain brain regions of the mouse [31].…”
Section: Paraquatmentioning
confidence: 99%
“…Some groups have reported no neurotoxic changes after paraquat exposure [28,32], whereas others have shown varying degrees of toxicity. For example, systemic paraquat exposure has been shown to cause a 20%-30% selective dopamine neuronal loss in the SNpc [33] and increased expression and aggregation of α-synuclein [33].…”
Section: Paraquatmentioning
confidence: 99%
“…The radioactive content was determined, 5min per sample, in a liquid scintillation counter (LS-6500, Beckman, USA), and the number of counts per minute detected in the plasma and in the brain tissue were expressed in nanomoles of 5-HT, based on the counts in the working solution of known concentration (N8). Times in the order of 10-15min are commonly used in studies of this type in mammals (Buschiazzo et al, 1970;Vitte et al, 1988;Naylor et al, 1995;Preston et al, 1995;Perasso et al, 2003) and fish . If a substance passes the BBB it will actually be detectable in the brain long before 15min.…”
Section: -Ht and The Blood-brain Barriermentioning
confidence: 99%